Secularly powered outflows from AGN: the dominance of non-merger driven supermassive black hole growth - Smethurst, R; Simmons, B; Lintott, C; Shanahan, J (Oxford University Press, 2019)
Recent observations and simulations have revealed the dominance of secular processes over mergers in driving the growth of both supermassive black holes (SMBH) and galaxy evolution. Here we obtain narrowband imaging of AGN powered outflows in a sample of 12 galaxies with disk-dominated morphologies, whose history is assumed to be merger-free. We detect outflows in 10/12 sources in narrow band imaging of the [OIII] 5007 A˚ emission using filters on the Shane-3m telescope. We calculate a mean outflow rate for these AGN of 0.95±0.14 M⊙ yr−1⁠. This exceeds the mean accretion rate of their SMBHs (⁠0.054±0.039 M⊙ yr−1⁠) by a factor of ∼18. Assuming that the galaxy must provide at least enough material to power both the AGN and the outflow, this gives a lower limit on the average inflow rate of ∼1.01±0.14 M⊙ yr−1⁠, a rate which simulations show can be achieved by bars, spiral arms and cold accretion. We compare our disk dominated sample to a sample of nearby AGN with merger dominated histories and show that the black hole accretion rates in our sample are 5 times higher (4.2σ) and the outflow rates are 5 times lower ( 2.6σ). We suggest that this could be a result of the geometry of the smooth, planar inflow in a secular dominated system, which is both spinning up the black hole to increase accretion efficiency and less affected by feedback from the outflow, than in a merger-driven system with chaotic quasi-spherical inflows. This work provides further evidence that secular processes are sufficient to fuel SMBH growth.